Assessing Scholarly Productivity - Hanish, Christine; Horan, John J.; Keen, Bethanne; Clark, Ginger (Education Policy Analysis Archives, 1998)
The measurement of scholarly productivity is embroiled in a controversy concerning the differential crediting of coauthors. Some researchers assign equivalent shares to each coauthor; others employ weighting systems based on authorship order. Horan and his colleagues use simple publication totals, arguing that the psychometric properties of labor-intensive alternatives are unknown, and relevant ethical guidelines for including coauthors are neither widely understood nor consistently followed. The PsycLIT and SSCI data bases provided exhaustive publication and citation frequencies for 323 counseling psychology faculty. All PsycLIT scoring permutations yielded essentially identical information; inter-correlations ranged from .96 to unity. Moreover, all PsycLIT methods correlated highly with SSCI within a very narrow band. Since attention to the number and/or ordinal position of coauthors yields no useful information, productivity should be defined parsimoniously in terms of simple publication counts. Implications for research, promotion/tenure, and the mentoring of graduate students are discussed.